STAGE DEPENDENT VARIABILITY IN TRACTIVE FORCE DISTRIBUTION THROUGH A RIFFLE-POOL SEQUENCE - Milan D.J.; Heritage G.L.; Large A.R.G.; Charlton M.E. (My University, 2001)
High resolution data on spatial and temporal variability in flow hydraulics and sediment transport within riffle-pool sequences are required to improve understanding of how fluvial processes maintain these meso-scale bedforms. This paper addresses this issue by providing velocity and boundary shear stress data over a range of discharges from base flow (0.07 m3 s-1) to just over bankfull (8.52 m3 s-1), from a sequence of four pools and three riffles in the River Rede, Northumberland. The data supports the reversal hypothesis of Keller [Geol. Soc. Am. Bull. 87 (1971) 753.] as the primary explanation for the maintenance of the riffle-pool sequence, although they also indicate that spatial variability in tractive force is highly stage dependent and complex. Section-averaged velocity data indicate reversal to be evident at four out of six riffle-pool units. An equalisation in velocity was found for the other two riffle-pool units close to bankfull stage. The spatial patterns of tractive force exhibited in the study reach as a result of increased discharge demonstrate that riffle-pool units operate independently of one another. Shear stress reversals were observed in individual riffle-pool units at different river stages during a flood hydrograph, and in some instances, two occurred in the same riffle-pool unit during a single flow event. Pools were characterised by coarser bed sediments and narrower channel widths in comparison to riffles, increasing the likelihood of tractive force reversal in the River Rede. Areas of predicted bed sediment entrainment obtained from τo-τc, matched observed channel changes in the upper part of the study reach, but over-estimated change in the middle portion of the reach.
Keywords: TRACTIVE FORCE; BOUNDARY SHEAR STRESS; GRAVEL-BED RIVER; VELOCITY REVERSAL HYPOTHESIS; RIFFLE-POOL; SEDIMENT TRANSPORT